Inhabitant’s View on Apartment Buildings Worldwide - Zunaira zafar; Salman Mahfooz; Talha Sabir; Iqra khalid (Riviera Publishing, 2024)
Apartment buildings are multi-unit buildings designed for residential purposes, where each unit or apartment is a stand-alone residential unit. Therefore, the purpose of this study is to identify the variables that influence residents' satisfaction with their living environment (which can include the neighborhood, type of residence, and social influences). The research method used is a qualitative method with descriptive data analysis techniques to identify trends and patterns of view preferences, sourced from participants' assessments/opinions of views from various apartment buildings. Many professionals, including scientists, medical experts, planners, biologists, and architects, have begun to explore the relationship between elements of the physical environment and the human experience along with urbanization and population growth. As a result, issues such as overcrowding, housing satisfaction, lack of sunlight, shared restrooms, and other issues have become the subject of scientific study.